Personalidad y síndrome del cuidador de niños en diálisis. Hospital Pediátrico Baca Ortiz Quito, 2022 - Bayas Lema, Gissela Vanesa (2022)
ABSTRACT: This research aimed to analyze the dimensions of the personality and the syndrome of the caregiver of children on dialysis at the "Baca Ortiz Pediatric Hospital" in Quito. The study was descriptive, correlational, bibliographic, field, and non-experimental, with a cross-sectional design. We worked with a sample of 150 people caring for children undergoing dialysis. The Eysenck Personality Questionnaire-Revised (EPQR-A) and the Zarit Caregiver Burden Scale were used for data collection. Data analysis was performed with the statistical program (SPSS) using the Spearman's Rho statistical correlation test, which determined a negative relationship between the extraversion dimension and caregiver overload. There was also a positive relationship between neuroticism and overload. The results indicate that 100% of the caregivers who participated in the research presented overload indexes according to the Zarit scale. In the same way, the caregivers obtained high and very high levels in the neuroticism dimension of 48.7% and 2.0 %, respectively. Through the data collection carried out, overload was identified at a mild and intense level, and the tendency of the participants to respond impatiently, apprehensively, emotionally, anxiously, shyly, and with low self-esteem, with feelings of guilt and sadness, as well as the influence exerted on them within mental health, therefore greater interest is suggested in relation to specialized psychological assistance programs for people in charge of care, so that in this way strategies are exercised that avoid the triggering of the syndrome of the caregiver and in turn generates an alteration in the quality of life. Keywords: dimensions, personality, overload, caregiver